Birmingham Paper - The Feasibility of using Cheaper Fuels in the Blast-Furnace. - Jacob T. Wainwright (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1889)
The object of this paper is to describe some efforts and observations by the writer relating to this subject. Althongh the usual type of' blast-furnace is a most efficient device for smelting and melting purposes, it is not suitable for utilizing the cheaper grades of fuel, such as coal-slack and certain gaseous fuels. This problem not only involves the consideration of the furnace as a suitable apparatus, but also embraces the consideration of the chemical and calorific properties of the proposed fuel. In the hearth of the ordinary blast-furnace an extremely high temperature is maintained. This extreme temperature is due to the complete combustion of the fuel in the hearth, and before the gases reach the zone of fusion their temperature is reduced, by the absorption of carbon, 2300 degrees Fat). In a smelting-furnace, the maintenance of this extreme temperature at the hearth becomes useless when it can be reduced without